Redescription of Asura toxodes Hampson, 1907 (Lepidoptera: Arctiinae: Lithosiini) after 117 years - Santosh Singh*; Navneet Singh; Jagbir Singh Kirti (Entomology Insights, 2024)
Abstract Asura Walker, 1854 is a large genus in the tribe Lithosiini subfamily Arctiinae of the Erebidae family. It is known for 61 species from the world out of which only a single species i.e., Asura toxodes Hampson, 1907 is known from India. Asura toxodes were described only on the basis of external morphology. Hence, in the present manuscript, we have redescribed Asura toxodes by external morphology and genitalic attributes in detail for the first time. Illustrations of the adult and its genitalia are provided.